The effect of migration on income growth and convergence: meta-analytic evidence - Ceren Ozgen; Peter Nijkamp; Jacques Poot (Institute for the Study of Labor (IZA), 2009)
We compare a set of econometric studies that measure the effect of net internal migration in neoclassical models of long-run real income convergence and derive 67 comparable effect sizes. The precision-weighted estimate of beta convergence is about 2.7%. An increase in the net migration rate of a region by one percentage point in increases the per capita income growth rate in that region on average by about 0.1 percentage points, thus suggesting an impact of net migration that is more consistent with endogenous self-reinforcing growth than with neoclassical convergence. Introducing a net migration variable in a growth regression increases the estimate of beta convergence slightly. Studies that use panel models or IV estimation methods yield smaller coefficients of net migration in growth regressions, while the opposite holds for regressions controlling for high-skilled migration.
Keywords: O15; O18; R23; R11; 330; Internal migration; economic growth; convergence; meta-analysis; neoclassical model; regional disparities; Binnenwanderung; Regionale Entwicklung; Entwicklungskonvergenz; Regionale Wachstumstheorie; Schätzung; Meta-Analyse; Welt